Minimal renal toxicity after Rituximab DHAP with a modified cisplatin application scheme in patients with relapsed or refractory diffuse large B-cell lymphoma - Kriegsmann, Katharina; Schöning, Tilman; Schwarzbich, Mark-Alexander; Cremer, Martin; Dittrich, Tobias; Ho, Anthony Dick; Witzens-Harig, Mathias (BMC cancer, 2016)
Rituximab (R) in combination with DHAP is a widely accepted salvage regimen for patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). A common adverse effect of this protocol is renal toxicity which may result in treatment discontinuation. Assuming that a lower single dose of cisplatin over several days would reduce renal toxicity, our institution has chosen to administer cisplatin in a dosage of 25 mg/m2 per day as a 3-h infusion over 4 consecutive days.